The Role of Lockups in Initial Public Offerings - Brav, Alon; Gompers, Paul A. (Review of Financial Studies, 2003)
In a sample of 2,794 initial public offerings (IPOs), we test three potential explanations for the existence of IPO lockups: lockups serve as (i) a signal of firm quality, (ii) a commitment device to alleviate moral hazard problems, or (iii) a mechanism for underwriters to extract additional compensation from the issuing firm. Our results support the commitment hypothesis. Insiders of firms that are associated with greater potential for moral hazard lockup their shares for a longer period of time. Insiders of firms that have experienced larger excess returns, are backed by venture capitalists, or go public with high-quality underwriters are more likely to be released from the lockup restrictions.